2013
DOI: 10.1070/qe2013v043n03abeh015029
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of yttrium oxide laser ceramics with additives

Abstract: A magnetic field has a remarkable influence on solid/solid phase transformations and it can be used to control the structure and function of materials during phase transformations. The effects of magnetic fields on diffusional solid/solid phase transformations, mainly from austenite to ferrite, in Fe-based alloys are reviewed. The effects of magnetic fields on the transformation temperature and phase diagram are explained thermodynamically, and the transformation behavior and transformed structures in magnetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 19 publications
0
10
0
3
Order By: Relevance
“…В них разупорядоченность кристаллической структуры проявляется в уширении полос излучения на лазерных переходах между штарковскими уровнями 4 (Fig.2, right). A complete overlap of the bands is observed at a minimum level of 0.25 of the maximum intensity with the width of the continuous band at this level reaching 100 nm on the base [11,12]. In the ceramics with additions of zirconium and hafnium, the trivalent Hf 3+ and Zr 3+ ions were found [11][12][13][14], which is confirmed by electron paramagnetic resonance spectra [13,14].…”
Section: керамики с разупорядоченной кристаллической структуройmentioning
confidence: 92%
See 1 more Smart Citation
“…В них разупорядоченность кристаллической структуры проявляется в уширении полос излучения на лазерных переходах между штарковскими уровнями 4 (Fig.2, right). A complete overlap of the bands is observed at a minimum level of 0.25 of the maximum intensity with the width of the continuous band at this level reaching 100 nm on the base [11,12]. In the ceramics with additions of zirconium and hafnium, the trivalent Hf 3+ and Zr 3+ ions were found [11][12][13][14], which is confirmed by electron paramagnetic resonance spectra [13,14].…”
Section: керамики с разупорядоченной кристаллической структуройmentioning
confidence: 92%
“…A complete overlap of the bands is observed at a minimum level of 0.25 of the maximum intensity with the width of the continuous band at this level reaching 100 nm on the base [11,12]. In the ceramics with additions of zirconium and hafnium, the trivalent Hf 3+ and Zr 3+ ions were found [11][12][13][14], which is confirmed by electron paramagnetic resonance spectra [13,14]. In the crystal, 3d 10 4d 1 Zr 3+ and 4f 14 5d 1 Zr 3+ ions form two Stark levels: the orbital doublet (E) and the triplet (T 2 ), with the energy gap equal to the strength of the crystal field in the positions of these ions.…”
Section: керамики с разупорядоченной кристаллической структуройmentioning
confidence: 99%
“…4b). According to [24], Zr 3+ ions could dramatically decrease the slope efficiency or even cause an absence of lasing in Zr 3+ -doped Nd 3+ 3. Sintering temperature.…”
Section: Microstructure Analysis and Optical Properties Of 0-4 At% Nmentioning
confidence: 99%
“…For example, in [23] it was found that stretching of the garnet crystal lattice at formation of the substitutional solid solutions Nd 3+ :YAG (r(Nd 3+ )>r(Y 3+ )) may lead to the formation of inclusions of the perovskite phases of general composition Y 1-х Nd х AlO 3 , while the use of SiO 2 additive allows one to compensate for this phenomenon (r(Si 4+ )<r(Al 3+ )). In [24,25] it was shown for ZrO 2 (HfO 2 )-Y 2 O 3 systems that the low concentration limit of existence of the substitutional solid solutions and the possibility to change the valence state of the heterovalent impurities lead to segregation of impurity phases along the grain boundaries, or to the degradation of the laser characteristics of ceramics due to quenching the upper energy levels and the laser levels…”
Section: Introductionmentioning
confidence: 99%
“…The second one is the Förster quenching of laser levels of Nd 3+ ions recently observed in rare earth sesquioxides. According to[57], Zr 3+ ions could dramatically decrease the slope efficiency or even cause an absence of lasing in ZrO 2 -doped Y 2 O 3 :Nd 3+ ceramics due to non-radiative energy transfer from the upper laser levels and pump levels of Nd 3+ ions to Zr 3+ acceptor levels. As it was illustrated above, no evidences of Zr 3+ ions were detected in sintered SiO 2 , ZrO 2 -doped YAG:Nd 3+ ceramics.…”
mentioning
confidence: 99%